The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1111/jace.16870
|View full text |Cite
|
Sign up to set email alerts
|

Wide‐bandgap HfO2‐V2O5 nanowires heterostructure for visible light‐driven photocatalytic degradation

Abstract: A novel HfO2/V2O5 nanocomposite has been fabricated for use as photocatalyst. HfO2 nanoparticles (NPs) were deposited on V2O5 using a precipitation method. Both commercial V2O5 particles and microwave‐assisted hydrothermal (MAH)‐synthesized V2O5 nanowires (NWs) were used. We demonstrate that the HfO2/V2O5 nanocomposite exhibits better photodegradation efficiency than the V2O5. The photodegradation reaction constant of the HfO2/V2O5 nanocomposite is more than 66% higher than that of the V2O5. The wide‐bandgap, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 64 publications
(124 reference statements)
0
8
0
Order By: Relevance
“…One important point relating to the band structure criteria is that the reduction potential of O 2 is less positive compared to CO 2 or H 2 O. Therefore, semiconductors with a relatively low conduction band position, such as WO 3 , V 2 O 5 , BiVO 4 , or Bi 2 WO 6 , were used in these stud-ies [54][55][56][57][58][59]. It is noted that Bi 2 WO 6 has no significant activity in the case of photocatalytic DRM, probably because of the insufficient conduction band potential [22].…”
Section: Methodsmentioning
confidence: 99%
“…One important point relating to the band structure criteria is that the reduction potential of O 2 is less positive compared to CO 2 or H 2 O. Therefore, semiconductors with a relatively low conduction band position, such as WO 3 , V 2 O 5 , BiVO 4 , or Bi 2 WO 6 , were used in these stud-ies [54][55][56][57][58][59]. It is noted that Bi 2 WO 6 has no significant activity in the case of photocatalytic DRM, probably because of the insufficient conduction band potential [22].…”
Section: Methodsmentioning
confidence: 99%
“…In this work, the authors indicated that the absence of luminescence led to a decrease in the scintillation light yield. Another application that benefits from the presence of oxygen vacancies concerns the photocatalytic degradation using inorganic NP heterostructures (HfO 2 –V 2 O 5 ; HfO 2 /TiO 2 ). , …”
Section: Introductionmentioning
confidence: 99%
“…The reason may be that the substitution of resident O atoms within the NaTaO 3 lattice by sulfur atoms induced the local states just above the valence level as the new hybridized orbitals were formed [12,40]. Aside from the bandgap width, the photocatalytic degradation activity of a sample highly depended on the recombination of electron (e − )-hole (h + ) pairs [12,[41][42][43][44]. Under photo-irradiation, the photo-induced e−/h+ pairs on the CB/VB of each semiconductor were created.…”
Section: Resultsmentioning
confidence: 99%